2018
DOI: 10.5194/wes-2018-10
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From lidar scans to roughness maps for wind resource modeling in forested areas

Abstract: Abstract. Applying erroneous roughness lengths can have a large impact on the estimated performance of wind turbines, particularly in forested areas. In this study, a new method called the Objective Roughness Approach (ORA), which converts tree height maps created using airborne lidar scans to roughness maps suitable for wind modeling, is evaluated via crosspredictions between different anemometers at a complex forested site with seven tall meteorological masts using the Wind Atlas Analysis and Application pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For the development of the socio-technical wind atlas, only constraints that are mentioned in multiple articles (>1) will be included. Forests are not viewed as a general constraint for wind power development, as previous studies have indicated how to overcome this challenge (Enevoldsen, 2018;Floors, et al, 2018).…”
Section: Ranking the Constraintsmentioning
confidence: 99%
“…For the development of the socio-technical wind atlas, only constraints that are mentioned in multiple articles (>1) will be included. Forests are not viewed as a general constraint for wind power development, as previous studies have indicated how to overcome this challenge (Enevoldsen, 2018;Floors, et al, 2018).…”
Section: Ranking the Constraintsmentioning
confidence: 99%